Growth and Yield Performance of Mustard and Rapeseed Varieties as Influenced by Different Sowing Techniques - Aziz, K M T; Razia, S; Ali, M H; Hasanuzzaman, M; Sourav, T A; Masum, S M (Bangladesh Agronomy Journal, 2024)
An experiment was conducted at the Agronomy field, Sher-e-Bangla Agricultural University, Dhaka, from November 2013 to February 2014 to investigate mustard and rapeseed varieties' growth and yield performances influenced by different sowing techniques. The experiment was laid out in a factorial randomized complete block design (RCBD) with three replications. The four varieties were BARI Sarisha-11, BARI Sarisha-13, BARI Sarisha-15, SAU Sarisha 2 (V1, V2, V3, and V4 respectively) and sowing techniques included broadcasting, line Sowing, raised bed, system of mustard intensification (SMI) (S1, S2, S3, and S4 respectively). Results showed that the highest plant height (143.58 cm) was achieved at the combination of BARI Sarisha-11 and the raised bed technique (V1S3) at harvest. Though the highest leaf number varied in different varieties, it was produced by the SMI technique. BARI Sarisha-15 and the SMI techniques produced the highest number of primary branches, though BARI Sarisha-11 produced the maximum secondary branches with the same technique. BARI Sarisha-11 performed best at all the DAS regarding dry matter accumulation (g) and the values resulting in 1.07, 11.44, 21.3, and 25.87g. SMI also proved to be the best, except for 30 DAS. The highest seed yield (3.74 t ha−1 and 3.80 t ha−1) was obtained using BARI Sarisha-11 and SMI techniques, respectively. The highest biological yields (12.80 t ha−1 and 12.86 t ha−1) were obtained by BARI Sarisha-11 and SMI technique, respectively. However, the maximum harvest index (34.84% and 32.45%) and highest oil percentages (40.65% and 41.38%) were obtained by BARI Sarisha-15 and line sowing, respectively. As such the var. BARI Sarisha-11 could be expected good yield following the SMI technique Bangladesh Agron. J. 2024, 26(2): 86-99